The indigo children new age experimentation with self and science - Singler, Beth (London New York Routledge, Taylor & Francis Group, 2018)
The indigo child -- Locating the indigo children -- The parental account of the indigo child -- Diagnosis and healing -- An indigo prophecy of the new age -- Reception, transmission, and parody -- The indigo race
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Gifted children; Generation Y; New Age movement